Tetrahydrobiopterin Protects Against Hypertrophic Heart Disease Independent of Myocardial Nitric Oxide Synthase Coupling - Toru Hashimoto; Vidhya Sivakumaran; Ricardo Carnicer; Guangshuo Zhu; Virginia S. Hahn; Djahida Bedja; Alice Recalde; Drew Duglan; Keith M. Channon; Barbara Casadei; David A. Kass (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundNitric oxide synthase uncoupling occurs under conditions of oxidative stress modifying the enzyme's function so it generates superoxide rather than nitric oxide. Nitric oxide synthase uncoupling occurs with chronic pressure overload, and both are ameliorated by exogenous tetrahydrobiopterin (BH4)—a cofactor required for normal nitric oxide synthase function—supporting a pathophysiological link. Genetically augmenting BH4 synthesis in endothelial cells fails to replicate this benefit, indicating that other cell types dominate the effects of exogenous BH4 administration. We tested whether the primary cellular target of BH4 is the cardiomyocyte or whether other novel mechanisms are invoked. Methods and ResultsMice with cardiomyocyte‐specific overexpression of GTP cyclohydrolase 1 (mGCH1) and wild‐type littermates underwent transverse aortic constriction. The mGCH1 mice had markedly increased myocardial BH4 and, unlike wild type, maintained nitric oxide synthase coupling after transverse aortic constriction; however, the transverse aortic constriction–induced abnormalities in cardiac morphology and function were similar in both groups. In contrast, exogenous BH4 supplementation improved transverse aortic constricted hearts in both groups, suppressed multiple inflammatory cytokines, and attenuated infiltration of inflammatory macrophages into the heart early after transverse aortic constriction. ConclusionsBH4 protection against adverse remodeling in hypertrophic cardiac disease is not driven by its prevention of myocardial nitric oxide synthase uncoupling, as presumed previously. Instead, benefits from exogenous BH4 are mediated by a protective effect coupled to suppression of inflammatory pathways and myocardial macrophage infiltration.